Grundtvigs almanak for aaret 1813 - Albeck, Gustav (Grundtvig-Studier, 1955)
Grundvig’s Calendar for 1813. Edited with comments by Gustav Albeck. In the Grundtvig Archives, Fasc. 505, there is preserved a little printed University Calendar “for the year 1813 after the birth of Christ”. Grundtvig had interleaved the little book with blue writing paper, by which means he had 14 pages altogether (28 sides) available for diary jottings, accounts, etc. — Some of the jottings have been used by Rönning and by Begtrup, but now they are all published as a whole for the first time. The least important items are a series of entries of accounts, which include, however, one curious point of interest, inasmuch as they reflect the violent devaluation which took place on the occasion of the “State bankruptcy” in January, 1813, since Grundtvig re-calculates the value of the so-called “bad money” at the new rate of exchange. The jottings in the book mirror the events after the death of Grundtvig’s father, the aged Pastor Johan Grundtvig, at Udby on January 5th. We get a glimpse of the last months spent by the family in the old parsonage, and the painful departure in October, when the mother went to Praestö and her son to Copenhagen. But still more important are the entries which are concerned with Grundtvig’s thoughts about his own future. He had been his father’s curate and did not inherit his living. In several passages in the Calendar he stresses the fact that he trusts that God will lead him to the place where he can accomplish most for the extension of God’s Kingdom. He himself is inclined to believe that that place is Norway, so that he can work in unison with his old friends from Walkendorffs Kollegium in Copenhagen, Hersleb and Sverdrup. To this end he seeks out the King (on his thirtieth birthday, September 8th) and asks for a Professorship at the new Norwegian University. A couple of months later he reads in a newspaper that the chaplaincy at Aggers Kirke (in Oslo) is vacant, and feels convinced that it is there that God wishes him to carry out his work. The Calendar in general reflects Grundtvig’s faith that God guides the world in accordance with a determined plan, and that everything happens in accordance with God’s will. With this little book we are in the middle of Grundtvig’s Biblical period. We see, too, from the notes that in the course of the year he read the New Testament through no less than five times.